Analisis kekerasan dan keausan bearing pada pesawat Cessna Grand Carravan 208B - Muhammad Abdul Rafiq Septiyanto; Indreswari Suroso; Noviana Utami (Universitas Muhammadiyah Metro, 2022)
Bearing is a surface component that protects two parts that rub against each other. Bearings have several components including inner rings, roll bearings and supports. Bearings will experience weariness when used continuously, so the purpose of this study is to determine the level of hardness and wear of each bearing component of the Cessna Grand Caravan 208B aircraft. Hardness testing is carried out by vickers method and test sampling is carried out at three different points in each specimen. Wear testing uses the Ogoshimethod and test sampling is performed at three different points in each specimen. The results of this study concluded that vickers hardness testing received the highest hardness score on the roll with an average value of 739.7 VHN, the second highest hardness in the inner ring had an average hardness value of 695.1 VHN, and the lowest hardness in the buffer section had an average hardness value of 110.2 VHN. The wear test results get the highest value on the support section which is 0.00273 mm³ / kg.m, the second highest wear on the inner ring is 0.00133 mm³ / kg.m, and the lowest wear value on the roll is 0.00056 mm³ / kg.m.